IL-33/ST2 axis in diverse diseases: regulatory mechanisms and therapeutic potential - Sheng, Feiya; Li, Mi; Yu, Jia-Mei; Yang, Si-Yu; Zou, Liang; Yang, Guan-Jun; Zhang, Le-Le (Frontiers in Immunology, 2025)
Interleukin-33 (IL-33) is a nuclear factor and member of the IL-1 cytokine family. IL-33 is mainly expressed by epithelial and endothelial cells and exerts its function through interaction with various immune cells, and binding to its receptor can form the IL-33/Suppression of tumorigenicity 2 (ST2) signaling pathway. While most cytokines are actively synthesized within cells, IL-33 is produced passively in response to tissue damage or cell necrosis, indicating its role as a signaling molecule following cellular infection, stress, or trauma. IL-33/ST2 signaling pathway has been proved to play diverse role in the pathological process of central nervous system disorders, cancer, fibrosis, autoimmune diseases, etc. Although research on the IL-33/ST2 signaling pathway has deepened recently, relevant treatment strategies have been proposed, and even targeted drugs are in the preclinical stage; further research on the effect of the IL-33/ST2 signaling pathway in different diseases is still necessary, to provide a clearer understanding of the different roles of IL-33/ST2 in disease progression and to develop new drugs and treatment strategies. Because IL-33/ST2 plays an important role in the occurrence and progression of diseases, the study of therapeutic drugs targeting this pathway is also necessary. This review focused on recent studies on the positive or negative role of IL-33/ST2 in different diseases, as well as the current related drugs targeting IL-33/ST2 in the preclinical and clinical stage. The mechanism of IL-33/ST2 in different diseases and its mediating effect on different immune cells have been summarized, as well as the antibody drugs targeting IL-33 or ST2, natural compounds with a mediating effect, and small molecule substances targeting relative pathway. We aim to provide new ideas and treatment strategies for IL-33/ST2-related drugs to treat different diseases.